TERATOGENESIS OF ANTIEPILEPTIC DRUGS: REVIEW AND CLINICAL CASES - D. V. Dmitrenko; N. A. Shnayder (Эпилепсия и пароксизмальные состояния)
Abstract: The article is devoted to problem of the teratogenic effects of antiepileptic drugs. The current approaches to refining birth defects in children whose mothers took the valproic acid drugs during pregnancy are described. The authors are presented the clinical cases for discussion.